The barriers and challenges of ISO 14001 environmental management system implementation in Malaysia industry - Lee, Li Fei (2016)
As the environmental issues that cause by human activities are getting concerned by the society, it is not only the responsibility of the government to support and conserve on the environment, but the organizations, entrepreneurs and people who live, occupy and involve in those activities for a better lifestyle should responsibility toward the earth. This article has fully summarized out the internal challenges and external barriers in implementing the Environmental Management System (EMS) ISO 14001 within organizations in order to raise the concern from organizations and government towards the environment. Total of 22 difficulties have been listed out through the literature review from previous researched. The data was successfully collected from 51 respondents at organizations that implement ISO 14001 that more than 3 years, those data have been analysed and successfully categorize 16 out of 22 difficulties into internal challenges and 6 difficulties as external barriers. Besides, all of those difficulties in both categorized were lay under the important factor level that should give an equal treatment and solutions to overcome those challenges and barriers with the mean that lay in between 2 to 3. These results provide a guideline for organizations and government to concern on the action should be taken in order to increase and maintain the number of organization in implementing ISO 14001. It is not that easy to implement EMS ISO 14001, however, the support and action taken in implementing EMS ISO 14000 from both the government and organizations may promote the success in achieving the ISO 14000 objectives and bringing the benefits for both parties and the earth.